Selective quantification of lacosamide in human plasma using UPLC–MS/MS: Application to pharmacokinetic study in healthy subjects with different doses - Bharwad, Kirtikumar D.; Shah, Priyanka A.; Shrivastav, Pranav S.; Sharma, Vinay S. (Biomedical chromatography, 2020)
A practical, sensitive, and robust UPLC–MS/MS method was developed and validated to quantify lacosamide in human plasma. A simple one‐step protein precipitation was used to extract lacosamide and labeled lacosamide‐13C, D3 as an internal standard (IS) from 150‐μL plasma. The extracts were analyzed on an Eclipse Plus C18 column (50 × 2.1 mm, 1.8 μm) using 0.1% formic acid in water and methanol:acetonitrile (50:50, v/v) under gradient conditions. The extracts were quantified on LCMS‐8040 using electrospray ionization source operated in positive ionization and multiple reaction monitoring modes. The method showed good linearity from 0.02 to 20 μg/mL, which was adequate to cover lacosamide concentration assayed in formulations with different strengths. The bioanalytical assay was fully validated as per current regulatory guidelines. The intra‐batch and inter‐batch precision values of lacosamide were less than 4.6%. Lacosamide was found to be stable at different storage conditions. The extraction recoveries and IS‐normalized matrix factors for lacosamide ranged from 97.17 to 99.68% and from 0.973 to 1.012, respectively. The validated method was successfully applied to a pharmacokinetic study with three lacosamide formulations (50, 100, and 200 mg) in 36 healthy subjects. The assay reliability was determined by reanalysis of 81 subject samples.